Women’s Political Representation and Intimate Partner Violence - Anukriti, S; Erten, Bilge; Mukherjee, Priya (Washington, DC : World Bank, 2022)
Recent studies demonstrate that female leaders can improve gender-specific outcomes along multiple dimensions through better provision of public goods and legislative changes that benefit women. Using quasi-random exposure to female leaders elected to state legislatures in India, this paper shows that there may also be an unintended effect: an increase in rural women’s reported experience of physical spousal abuse. We find that a plausible channel underlying this effect is an increase in women’s modern contraceptive use—potentially resulting from improvements in public provision of health services—which leads to marital conflict, especially when the husband’s son preference is stronger than the wife’s.